Turkey : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Turkey's economy has grown on average by 6 percent annually since 2010, but this has come at the expense of a large external deficit, making the economy sensitive to changes in external financing conditions. Macroeconomic policies have been too accommodative, inflation is high and well above the authorities' target, real policy interest rates remain negative, and the exchange rate continues to be stronger than suggested by fundamentals. The main risk for Turkey remains a capital flows reversal, associated with monetary policy normalization in advance economies or changes in the country risk premium. Other risks center on slower European growth, geopolitical issues, and the strength of the policy framework.